2023
DOI: 10.3390/jfb14010044
|View full text |Cite
|
Sign up to set email alerts
|

Icariin: A Promising Natural Product in Biomedicine and Tissue Engineering

Abstract: Among scaffolds used in tissue engineering, natural biomaterials such as plant-based materials show a crucial role in cellular function due to their biocompatibility and chemical indicators. Because of environmentally friendly behavior and safety, green methods are so important in designing scaffolds. A key bioactive flavonoid of the Epimedium plant, Icariin (ICRN), has a broad range of applications in improving scaffolds as a constant and non-immunogenic material, and in stimulating the cell growth, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 172 publications
0
7
0
Order By: Relevance
“…The bioactive molecules of traditional Chinese medicine such as icariin, drynaria, salvia miltiorrhiza, etc., have a certain role in promoting bone repair, and the sustained release of these traditional Chinese medicines by the nanocellulose-based aerogels might have promising potential for bone regeneration [ 150 , 151 ]. Resveratrol (Res) is a phenolic compound with a chemical formula of C14H12O3.…”
Section: Nanocellulose Aerogels-based Controlled Releasing System For...mentioning
confidence: 99%
“…The bioactive molecules of traditional Chinese medicine such as icariin, drynaria, salvia miltiorrhiza, etc., have a certain role in promoting bone repair, and the sustained release of these traditional Chinese medicines by the nanocellulose-based aerogels might have promising potential for bone regeneration [ 150 , 151 ]. Resveratrol (Res) is a phenolic compound with a chemical formula of C14H12O3.…”
Section: Nanocellulose Aerogels-based Controlled Releasing System For...mentioning
confidence: 99%
“…Icariin/ICA is a flavonoid bioactive produced from the roots and leaves of the Epimedii herb, which is used to treat a number of ailments. Extracts of Epimedii herbs contain several bioactivities, including the capacity to prevent cancer cell invasion and migration, improve sexual function and memory, raise phytoestrogen activity, boost immunology, and have anti-inflammatory qualities 1 Gao et al found that the use of ICA to induce apoptosis and reduce invasion of triplenegative breast cancer (TNBC) was successful in silico and in vitro. 2 Nonetheless, findings were studied, evaluated, and merited greater discussion in the study and treatment strategies reported in this paper.…”
Section: Dear Editormentioning
confidence: 99%
“…For example, genistein may exhibit estrogen-like effects to protect against many diseases, such as cancers, osteoporosis (OP), and OA [9]. Icariin shows promising characteristics in biomedicine and bone/cartilage tissue engineering [10]. Naringin (4 , 5,7-trihydroxy flavanone-7-rhamnoglucoside, Figure 1) is a flavonoid glycoside that is found in the extract of citrus fruits [11] and rhizoma drynariae [12].…”
Section: Introductionmentioning
confidence: 99%